Nadhariyat Nashatul al-Lughah wa Furudhiyan Asbab Intisyaruha - Fina Aunul Kafi (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2021)
The beginning of language and how language spreads remain an unsolved puzzle to this day. Even a number of scholars have likened the objective of solving this problem due to lack of data and tend to be speculative. Religionists and scientists have their own beliefs in the idea of the beginning of language and its spread. The theories of the beginning of language also have their own foundation of truth. This research aims to re-map how languages began and spreaded along with human development. Researcher used a qualitative descriptive method by extracting data through the literature. The results of this study are that there are two major theories that dominate this problem field, namely the theory which states that language is a gift from God and another theory states language is the result of human creation. The many theories that are related to this issue will be pointed at the two camps. Keywords: God, language, tauqify, theory